Lower grain nitrogen content of wheat at elevated CO2 can be improved through post-anthesis NH4+ supplement. (March 2017) - Fernando, Nimesha; Hirotsu, Naoki; Panozzo, Joe; Tausz, Michael; Norton, Robert M.; Seneweera, Saman
Abstract: We test the hypothesis that reduction in grain N concentration under elevated CO2 concentration (e[CO2 ]) is associated with N types (NH4 + and NO3 − ) and their ratios. Wheat ( Triticum aestivum L. cv. H45) was grown in a glasshouse under two CO2 concentrations (389 μmol mol −1 and 700 μmol mol −1 ), supplied with equal amount of N with different ratios of NH4 + and NO3 − : (i) 100% NO3 − –N; (ii) 50% NO3 − –N and 50% NH4 + –N; and (iii) 25% NO3 − –N and 75% NH4 + –N. Plant growth, N uptake and partitioning were measured during plant development. Plant biomass and grain yield was increased at e[CO2 ] when N was supplied as an equal proportion of NO3 − and NH4 + . Despite the yield increment, grain N concentration was not affected by e[CO2 ], in 50% NO3 − –N treatment. In contrast, grain N concentration decreased in 100% NO3 − –N and 25% NO3 − –N treatments. In 50% NO3 − –N treatment, N uptake during post-anthesis stage (from 69 to 141 days after planting) was significantly stimulated under e[CO2 ] compared to 100% NO3 − –N and 25% NO3 − –N treatments. We concluded that supplement of N in an equal proportion of NO3 − and NH4 + which increases post-anthesis N uptake, avoid the reduction of grain N concentration under e[CO2 ]. Highlights: Reduction in grain N at e[CO2 ] is associated with N type and ratio during plant growth was tested. Wheat was grown at 2 CO2 levels: a[CO2 ] and e[CO2 ], supplied equal amount of N in 3 ratios of NH4 + and NO3 − Plant growth, N uptake, N partitioning were measured during growth. Despite yield increment at e[CO2 ], grain N concentration were not affected by e[CO2 ], in 50% NO3 − –N treatment. N uptake after anthesis is the key determinant of grain N content under e[CO2 ].